ACCOUNTING PARADIGMS WHICH FAVOR HISTORICAL COST - Valentin Gabriel CRISTEA (Challenges of the Knowledge Society)
Henning Kirkegaard shows that the evolution of accounting is to shift from one paradigm to another . Business continuity perspective should guide the company into the future , without confine it exclusively in the past. Accounting in its classical form , however, can not be dissociated from the historical cost evaluation .